Regional Stabilization by Fiscal Equalization? Theoretical Considerations and Empirical Evidence from Germany - Thiess Büttner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In the context of EMU fiscal equalization schemes have been proposed as a means to stabilize regions against asymmetric shocks. A theoretical analysis shows that besides reducing the cross-sectional income variance the redistributive element of fiscal equalization causes incentive effects for regional governments, undermining the efficient supply of public goods. Yet, this objection is shown to be less important in a situation of insufficient demand, where interregional redistribution actually favors stabilization. In an empirical analysis for Germany, the paper adds support for the finding of significant regional stabilization by fiscal flows. The results indicate that about 17 % of GDP variation across West Germany's states has been removed by fiscal flows during the last two decades. Thus, in Germany where the fiscal federalism is criticised for its heavy equalization the extent of regional stabilization provided by fiscal flows is quite similar to other federal countries.
Keywords: F15; H77; R11; E62; 330; Finanzausgleich; Regionale Disparität; Ökonomischer Anreiz; Regionale Entwicklung; Theorie; Schätzung; Deutschland